PRESERVATION, STUDY AND DISSEMINATION OF THE TRADITIONAL DOMBRA ART OF THE KAZAKHS (ON THE EXAMPLE OF KUISHI KOZHEKE NAZARULY) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
One of the priority tasks of the world community is the preservation of world cultural heritage, including intangible cultural heritage, which includes musical folklore. In the context of the Turkic-language instrumental musical heritage, special attention is paid to the Kazakh dombra art, especially in the Zhetysu region (southern Kazakhstan). This art preserves unique cultural and regional characteristics, being an important element of national identity. The article examines the traditional dombra art using the example of the work of kuyshi Kozheke Nazaruly, with an emphasis on the shertpe style. Preservation of traditions requires a comprehensive approach: from accurate reproduction of musical material to the introduction of new elements, while preserving the cultural flavor. Another important aspect is the use of traditional elements in the modern life of Kazakhs.The author classifies Kozheke’s kuis and emphasizes their connection with the folklore tradition. The study confirms the presence of instrumental “doubles” of ritual genres in the work of kuyshi. The importance of Kozheke’s professional status as a kuyshi and batyr is revealed in the context of socio-historical events. The article also highlights the problem of improvisation and variability in the performance of dombra kuys, which plays a key role in the preservation and dissemination of folk musical heritage.
Keywords: kuy; kuyshi Kozheke Nazaruly; traditional instrumental music; dombra art of the Kazakhs; shertpe style; regional specificity.